SIGNIFICANCE OF TACROLIMUS MONITORING TO OPTIMIZE IMMUNOSUPPRESSIVE THERAPY - PARVEEN POPLI,; PRANAV KUMAR PRABHAKAR, (International Journal of Pharma and Bio Sciences, 2015)
Liver transplantation is the surgical treatment of choice for several irreversible liver diseases where a partially or completely diseased liver is replaced with a healthy liver. The continued use of immunosuppressant causes certain serious consequences such as hepatotoxicity, nephrotoxicity and post-transplant hyperglycemia. Inter individual variation has necessitated frequent monitoring of tacrolimus concentration to prevent toxicity, which is the major clinical challenge encountered in the post-transplant period. This study was carried out with the aim to evaluate the correlation between blood concentration of tacrolimus and the risk/degree of toxicity with time after liver transplant. Our data suggests that monitoring effective immunosuppression is essential to minimize toxicity induced by tacrolimus, especially in the 3-6 month period. Therefore, it is necessary to maintain trough blood concentration in liver transplant recipient’s 10-12 ng/ml in first trimester, 8-10 ng/ml in next trimester and 5-8 ng/ml thereafter. Hence, monitoring of tacrolimus concentration of the recipient should be done throughout the period of tacrolimus intake i.e. for life time, to enhance clinical evaluation.